2004
DOI: 10.1542/peds.114.1.e102
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence Policies and Other Predictors of Asthma Care Quality for Medicaid-Insured Children

Abstract: ABSTRACT.Objective. More than half of Medicaid enrollees are now in managed care. Scant information exists about which policies of practice sites improve quality of care in managed Medicaid. Children with asthma are a sentinel group for Medicaid quality monitoring because they are at elevated risk for adverse outcomes. The objective of this study was to identify practice-site policies and features associated with quality of care for Medicaid-insured children with asthma.Methods. A prospective cohort study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 32 publications
(31 reference statements)
1
62
0
Order By: Relevance
“…These findings are consistent with those of Lieu et al 24 , who demonstrated that parent-reported asthma outcomes are better when children receive care in settings with more racially concordant staff. Non-concordance of staff was associated with more perceived disrespect, indicating that cultural sensitivity training may be needed for all health care staff members.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with those of Lieu et al 24 , who demonstrated that parent-reported asthma outcomes are better when children receive care in settings with more racially concordant staff. Non-concordance of staff was associated with more perceived disrespect, indicating that cultural sensitivity training may be needed for all health care staff members.…”
Section: Discussionsupporting
confidence: 91%
“…For comparison, rates of successful reinterviewing of parents in longitudinal telephone surveys ranged from 68% to 85% in recently published investigations. 44,45 It is important to recognize that survey respondents might have differed from nonrespondents in ways that might influence our findings. Our data showed that respondents were more likely to have received influenza vaccine in a study practice, compared with nonrespondents.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors contributing to racial differences in adverse outcomes may include more-severe disease, variations in disease phenotypes and responsiveness to medication, environmental exposures, lag in uptake of medical advances to control asthma symptoms among health care providers who treat minority children, lack of cultural competence policies among health care providers, and lack of asthma education or difficulties in adopting certain asthma control methods for minority race/ethnic families. 44,71 Improving Outcomes for All Children With Asthma Is an Achievable Goal Removing the adverse impact of asthma in the life of a child is an achievable but demanding goal. Recognizing early symptoms, avoiding asthma triggers, arranging appropriate health care, and managing the schedule of medication administration can be complex for children and their families.…”
Section: Minority Children Have a Critical Need For Improved Intervenmentioning
confidence: 99%
“…44 Improvements in asthma care quality among medical practices using cultural competence policies have already been demonstrated. 71 Although bringing such promising interventions to effective and widespread use poses a great challenge, doing so should be part of the public health response to asthma.…”
Section: Minority Children Have a Critical Need For Improved Intervenmentioning
confidence: 99%